A universal trade-off between growth and lag in fluctuating environments - Basan, Markus; Honda, Tomoya; Christodoulou, Dimitris; Hörl, Manuel; Chang, Yu-Fang; Leoncini, Emanuele; Mukherjee, Avik; Okano, Hiroyuki; Taylor, Brian R.; Silverman, Josh M.; Sanchez, Carlos; Williamson, James R.; et al. (Nature (London), 2020)
The rate of cell growth is crucial for bacterial fitness and drives the allocation of bacterial resources, affecting, for example, the expression levels of proteins dedicated to metabolism and biosynthesis 1 , 2 . It is unclear, however, what ultimately determines growth rates in different environmental conditions. Moreover, increasing evidence suggests that other objectives are also important 3 – 7 , such as the rate of physiological adaptation to changing environments 8 , 9 . A common challenge for cells is that these objectives cannot be independently optimized, and maximizing one often reduces another. Many such trade-offs have indeed been hypothesized on the basis of qualitative correlative studies 8 – 11 . Here we report a trade-off between steady-state growth rate and physiological adaptability in Escherichia coli , observed when a growing culture is abruptly shifted from a preferred carbon source such as glucose to fermentation products such as acetate. These metabolic transitions, common for enteric bacteria, are often accompanied by multi-hour lags before growth resumes. Metabolomic analysis reveals that long lags result from the depletion of key metabolites that follows the sudden reversal in the central carbon flux owing to the imposed nutrient shifts. A model of sequential flux limitation not only explains the observed trade-off between growth and adaptability, but also allows quantitative predictions regarding the universal occurrence of such tradeoffs, based on the opposing enzyme requirements of glycolysis versus gluconeogenesis. We validate these predictions experimentally for many different nutrient shifts in E. coli , as well as for other respiro-fermentative microorganisms, including Bacillus subtilis and Saccharomyces cerevisiae . A model of sequential flux bottlenecks explains a universal trade-off between steady-state growth and physiological adaptation time in bacteria exposed to fluctuating growth conditions.